Formation of Correct Reading Skills in Primary School Students - Shakhmurodova Diljakhon Almardonovna (Genius Publishing Group, 2022)
The article deals with the formation of correct reading skills in elementary school students. The content of the goals and types of training is explained
Keywords: Reading; fast; conscious; expressive